Wife as the Main Breadwinner from Islamic Law Perspective : (Study in Pekalongan Regency) - Aini, Fida; Mohammad Hasan Bisyri (Al-Hukkam: Journal of Islamic Family Law, 2024)
The phenomenon of the wife's role being involved as the main breadwinner in the family occurred in Dukuh Wijo, Getas Village, Wonopringgo District, Pekalongan Regency. The aim of this research is, among other things, to examine the Islamic law review of the patterns and principles of fulfilling a living in the family of a wife who has the status of the main breadwinner in Dukuh Wijo, Getas Village. This type of research includes field research. This research uses a qualitative approach. The data sources for this research are the results of interviews, observations, and other supporting literature. This research data collection technique uses interview, observation, and documentation techniques. This research analysis uses descriptive analysis techniques. The results of this research include: (1) The main breadwinner's wife's livelihood fulfillment pattern is divided into two, namely, the wife fulfills her livelihood in full and some only partially. (2) The reason why wives persist in their role as main breadwinners is because wives have the principle of maintaining their marital commitment and prioritizing the interests of their children's future. (3) According to Islamic law, it is sunnah, fardhu and permissible for a wife to work and change her role to become the main breadwinner. The conditions experienced by the eight main breadwinner wives are seen based on the level of need, namely dharuriyyat, hajjiyat or tahsiniyat.